PENERAPAN APLIKASI WEB UNTUK ADMINSTRASI DI DESA SIDOSARI LAMPUNG SELATAN - Jaka Persada Sembiring (Journal of Social Sciences and Technology for Community Service (JSSTCS), 2022)
Correspondence services and civil registration of the population are very important in village administration. In this case, Sidosari village provides services including correspondence services and population registration for the Sidosari village community. Based on interviews with representatives of village staff that have been carried out at the Sidosari village office, they said that there are several shortcomings in the service section at the Sidosari village office, one of which is the correspondence service and population registration which is done manually. In this case the correspondence service is done manually causing data and letters that have been made difficult to find and frequent data loss occurs. This website is expected to be a tool for employees in carrying out their duties to serve and record population in Sidosari village, South Lampung. Keywords: Administration, Village, Website.